2014
DOI: 10.4253/wjge.v6.i9.432
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of YouTube™ videos related to bowel preparation for colonoscopy

Abstract: AIM:To examine YouTube™ videos about bowel preparation procedure to better understand the quality of this information on the Internet. METHODS:YouTube™ videos related to colonoscopy preparation were identified during the winter of 2014; only those with ≥ 5000 views were selected for analysis (n = 280). Creator of the video, length, date posted, whether the video was based upon personal experience, and theme was recorded. Bivariate analysis was conducted to examine differences between consumers vs healthcare pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
1
29
0
1
Order By: Relevance
“…11 Kofinas et al 14 found that SM could improve patient contraceptive knowledge in a randomized controlled study. Although information associated with the quality of colonoscopy (including bowel preparation) could be easily found in several SM platforms (YouTube, 15 Facebook, Twitter, and Wechat, etc), it remains unknown whether it could be used to improve the adequacy of bowel preparation and the quality of colonoscopy. Here we conducted a prospective, randomized controlled trial at 3 centers.…”
Section: Discussionmentioning
confidence: 99%
“…11 Kofinas et al 14 found that SM could improve patient contraceptive knowledge in a randomized controlled study. Although information associated with the quality of colonoscopy (including bowel preparation) could be easily found in several SM platforms (YouTube, 15 Facebook, Twitter, and Wechat, etc), it remains unknown whether it could be used to improve the adequacy of bowel preparation and the quality of colonoscopy. Here we conducted a prospective, randomized controlled trial at 3 centers.…”
Section: Discussionmentioning
confidence: 99%
“…The medium has been used for a wide range of purposes, including the creation of educational materials for health care professionals [9], the generation of a patient community where discussion about experiences and treatment can occur [10], the documentation of patient experiences for side-by-side health communication messages [11], and personal barriers to accessing care [12]. The platform provides a unique mix of social media and visual representation that can create confusion in regard to the quality of health information available.…”
Section: Discussionmentioning
confidence: 99%
“…The platform provides a unique mix of social media and visual representation that can create confusion in regard to the quality of health information available. One study reported on the unreliability and misleading nature of the information presented on the website [13], while another has shown that the majority of condition specific videos are generally consistent with medical recommendations [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Basch et al . [ 9 ] analyzed 280 videos on bowel preparation and found that: Professional-created videos had more views (focusing on purgative type and completing the preparation) and consumer-created ones had more comments (emphasizing palatability, disgust, and hunger during the procedure) which would have direct impact on attitudes toward colon cancer screening.…”
Section: Youtube and Palliative Care Practicementioning
confidence: 99%